2004
DOI: 10.1021/jm030505a
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 2-(4-Pyridin-2-ylpiperazin-1-ylmethyl)-1H-benzimidazole (ABT-724), a Dopaminergic Agent with a Novel Mode of Action for the Potential Treatment of Erectile Dysfunction

Abstract: A new class of agents with potential utility for the treatment of erectile dysfunction has been discovered, guided by the hypothesis that selective D4 agonists are erectogenic but devoid of the side effects typically associated with dopaminergic agents. The lead agent 2-(4-pyridin-2-ylpiperazin-1-ylmethyl)-1H-benzimidazole (1, ABT-724) was discovered by optimization of a series of benzimidazole arylpiperazines. This highly selective D4 agonist was found to be very potent and efficacious in vivo, eliciting peni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Furthermore, the functional properties of L750,667, PNU101,387G, ABT-724, and Ro10-5824 for the mutant receptors were the same as for the wild-type receptors: they were all antagonists because they did not activate the receptors and prevented activation by the agonist (Ϫ)-quinpirole. Two of the D4-selective ligands used in this study, ABT-724 and Ro10-5824, have been reported to possess partial agonist properties when using either [ 35 S]GTP␥S binding or FLIPR assays as functional end points (Powell et al, 2003;Cowart et al, 2004;Newman-Tancredi et al, 2008). However, using intracellular cAMP accumulation as a functional endpoint we found that ABT-724 and Ro10-5824 lacked agonist properties, but antagonized (Ϫ)-quinpirole activation in wild-type and mutant receptors.…”
Section: Resultsmentioning
confidence: 60%
“…Furthermore, the functional properties of L750,667, PNU101,387G, ABT-724, and Ro10-5824 for the mutant receptors were the same as for the wild-type receptors: they were all antagonists because they did not activate the receptors and prevented activation by the agonist (Ϫ)-quinpirole. Two of the D4-selective ligands used in this study, ABT-724 and Ro10-5824, have been reported to possess partial agonist properties when using either [ 35 S]GTP␥S binding or FLIPR assays as functional end points (Powell et al, 2003;Cowart et al, 2004;Newman-Tancredi et al, 2008). However, using intracellular cAMP accumulation as a functional endpoint we found that ABT-724 and Ro10-5824 lacked agonist properties, but antagonized (Ϫ)-quinpirole activation in wild-type and mutant receptors.…”
Section: Resultsmentioning
confidence: 60%
“…In vivo administration to rats to test potential treatment of erectile dysfunction [184,185] WAY 100635 16.4 D4 receptor agonist and 5HT1A antagonist; produces discriminative stimulus effects in rats [186,187] PD 168077 8.7 Selective D4 agonist, proerectile effect in rats [188]; tested in mice for memory consolidation studies [189] PNU 96415E 3 Tested for antipsychotic potential [190] Ro 10-5824 5.2 Selective D4 agonist, increases novel exploration in mice [191] NGD 94-1 3…”
Section: Dopamine-related Diseasesmentioning
confidence: 99%
“…ABT-724 is a selective dopamine D4 receptor agonist, which successfully induced penile erection in a rat model without side effects such as nausea and emesis (13). ABT-670 is known to have better oral bioavailability than ABT-724 while having similar efficacy (14).…”
Section: Clinical Trials To Develop Ed Therapeutics Targeting Alternamentioning
confidence: 99%